β2-and β3-Adrenergic Receptors Contribute to Cancer-Evoked Pain in a Mouse Model of Osteosarcoma via Modulation of Neural Macrophages - Bruno, Gennaro; De Logu, Francesco; Souza Monteiro de Araujo, Daniel; Subbiani, Angela; Lunardi, Federica; Rettori, Sofia; Nassini, Romina; Favre, Claudio; Calvani, Maura (Frontiers in Pharmacology, 2021)
The mechanisms involved in the development and maintenance of cancer pain remain largely unidentified. Recently, it has been reported that β-adrenergic receptors (β-ARs), mainly β2-and β3-ARs, contribute to tumor proliferation and progression and may favor cancer-associated pain and neuroinflammation. However, the mechanism underlying β-ARs in cancer pain is still unknown. Here, we investigated the role of β1-, β2-and β3-ARs in a mouse model of cancer pain generated by the para-tibial injection of K7M2 osteosarcoma cells. Results showed a rapid tumor growth in the soft tissue associated with the development of mechanical allodynia in the hind paw ipsilateral to the injected site. In addition to reduce tumor growth, both propranolol and SR59230A, β1-/β2-and β3-AR antagonists, respectively, attenuated mechanical allodynia, the number of macrophages and an oxidative stress by-product accumulated in the ipsilateral tibial nerve. The selective β1-AR antagonist atenolol was able to slightly reduce the tumor growth but showed no effect in reducing the development of mechanical allodynia. Results suggest that the development of the mechanical allodynia in K7M2 osteosarcoma-bearing mice is mediated by oxidative stress associated with the recruitment of neural macrophages, and that antagonism of β2-and β3-ARs contribute not solely to the reduction of tumor growth, but also in cancer pain. Thus, the targeting of the β2-and β3-ARs signaling may be a promising therapeutic strategy against both tumor progression and the development of cancer-evoke pain in osteosarcoma.